REDUPLIKASI BAHASA MELAYU RIAU DIALEK KAMPAR - Dina Zulfri Yanti; Hasnah Faizah AR; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study examines the Reduplication in Riau Malay Dialects Kampar. This study aimed to describe the forms of reduplication morphemic Riau Malay Dialects Kampar and describe the meaning of reduplication morphemic dialect of Malay Riau Kampar. This research is descriptive research that provides an objective picture of the Riau Malay language dialects reduplication Kampar by using the speech is authentic (valid) by the speakers today. This research data in the form of speech uttered by the informant in the village Alampanjang research in which there reduplications use. Informants in this study is the Kampar are indigenous people and has long been domiciled in kenegrian Kampar, in order to obtain reliable information in the research effort is in need of criteria of which number as many as ten people informant and the informant criteria. The data collection is done by observing, interviewing and recording. Informants in this study as many as ten people who have met the study criteria. Data were analyzed with descriptive method, the data analyzed in the form of dialect words Kampar used as a means of communication by the public Kampar.Keywords: reduplication, dialect, morphemic..